Design, Teaching, and Assessment of an English for Specific Purposes Course for Tourism Students - Segura Arias, Róger (2025)
This study outlines the steps to develop an English for Specific Purposes (ESP) course for tourism students at the National University, Brunca Regional Headquarters, Pérez Zeledón Campus. The course was developed as part of a capstone project for the Master's program in Applied Linguistics. The resulting deliverable was a course that targeted English used at hotel reception desks. This endeavor can serve as a baseline for future ESP projects in the tourism sector. This article details the design, teaching, and subsequent assessment of an English for Occupational Purposes course. The course aims to meet the specific needs of tourism students by providing language training focusing on tasks and scenarios at the hotel reception desk. The information necessary to design the course was compiled through the use of questionnaires, interviews, and surveys answered by students, employers, alumni, and instructors. Based on the results, the "English for Hotel Reception Desk" course, designed under an English for Occupational Purposes (EOP) and a Task-based Approach methodology, effectively addressed specific on-the-job tasks carried out by hotel receptionists. Despite the challenge of teaching a large class size online, students displayed high levels of engagement and improved language skills, supported by collaboration with industry experts and positive course evaluations.